Production dynamics of Cenococcum geophilum ectomycorrhizas in response to long-term elevated CO2 and N fertilization. (April 2017) - McCormack, M. Luke; Fernandez, Christopher W.; Brooks, Hope; Pritchard, Seth G.
Abstract: Ectomycorrhizal fungi are important in many forest ecosystems, yet their production dynamics and responses to environmental changes are poorly understood. Cenococcum geophilum is a common ectomycorrhizal fungus important to plant and forest soil biogeochemical cycles. The seasonal and inter-annual patterns of production and persistence of mycorrhizas formed by C. geophilum in a pine forest exposed to elevated atmospheric CO2 and nitrogen fertilization were monitored using a 12 y minirhizotron dataset. Production of C. geophilum mycorrhizas was distinctly seasonal and peaked in late summer/autumn. Elevated CO2 generally increased production while nitrogen fertilization strongly decreased production. Persistence times of C. geophilum mycorrhizas was ca. 2.7 y and was unaffected by CO2 and nitrogen addition. Total production was greater in shallow soil (0–16 cm) but persistence was longer in deeper soil (17–32 cm). These observations provide insights into the autecology of C. geophilum and suggest that its tissues may be slow to decompose compared to other ectomycorrhizal species.